(3GdagQSJ (B( (3dcJH GdTjYI (B)s - (3eMeO Hf GdMSf Hf Ydj GdWhSj , CHh LYaQ,J (B460 (3g` s ((3eMeO Hf CNj eMeO GdcGJH s)
(3ChdgG (B:s
(3CeG HYO , aEfi deG QCjJ LeGYI ef TjN WGFaJfG ef CUMGH GdMOjK , YedhG agQSJ cJH CUMGHfG hde CLO CMOkG efge GSJhai Pdc s
(3BNQgG (B:s
(3GHf YUGe (B: (3dg fhGOQ CNHQfG LeGYI Yf CHj GdeaVd Yf MejO Yf GHf YUGe Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B84 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B202s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B315 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs